An energy-efficient hybrid wireless mesh protocol (HWMP) for IEEE 802.11s mesh networks - Ng, Ming Ann *; Yau, Alvin Kok-Lim * (2013)
The existing path selection scheme in IEEE 802.11s for wireless mesh networks is Hybrid Wireless Mesh Protocol (HWMP). The main routing metric of HWMP is called airtime metric, which is dependent on packet error rate and transmission bitrate. HWMP does not take energy efficiency into consideration despite its importance for mobile nodes and other nodes which are battery driven. In our proposed energy-efficient HWMP(eHWMP) scheme, in addition to airtime metric, we incorporate per-hop delay and residual energy into the routing metric in order to increase energy efficiency without jeopardizing end-to-end delay performance. Preliminary simulation results show that eHWMP achieves our objective by increasing network lifetime without causing significant effects on end-to-end delay and throughput as compared to the traditional HWMP.